Streptococcus pneumoniaeand lytic antibiotic therapy: are we adding insult to injury during invasive pneumococcal disease and sepsis?. Issue 8 (August 2017) - Brown, Lauren April; Mitchell, Andrea M.; Mitchell, Tim J.
Abstract : Abstract : Streptococcus pneumoniae ( S. pneumoniae ), otherwise known as 'the pneumococcus', is a fascinating microbe that continues to pose a significant problem to public health. Currently there are no specific National Institute for Clinical Excellence (NICE) or British Thoracic Society (BTS) clinical guidelines referring to the treatment of invasive pneumococcal infection. NICE clinical guidelines suggest the use of lytic β‐lactam antibiotic regimens for the management of community‐acquired pneumonia and bacterial meningitis; infections for which S. pneumoniae is a likely causative organism. Lytic antibiotics have been shown to increase the release of pneumolysin (the highly inflammatory and damaging toxin of the pneumococcus), thus theoretically increasing host damage, which may lead to a decline of clinical outcomes in vulnerable patients. In light of this information, should the use of non‐lytic antibiotics, such as quinolones, rifamycins and macrolides, be considered for the treatment of invasive pneumococcal disease?